Interdependence between climate change and migration: Does Agriculture, geography and development level matter in sub-Saharan Africa? - Frank Bannor; Isaiah Hubert Magambo; Jugal Mahabir; Jean-Luc Mubenga Tshitaka (ZBW - Leibniz Information Centre for Economics, 2022)
Concerns about the human effects of climate change have contributed to forecasts of how populations in drought-prone, and flood-prone areas would respond to these events. Empirical studies have predicted that human migration has been among the critical resilient strategy in responding to the impact of climate change. To obtain a more comprehensive understanding of the climate–migration relationship, the impacts of climate change on international migration flows from Sub-Saharan Africa (SSA) nations to South Africa are investigated empirically in this paper. The study employed a fixed effects model and panel data from 35 countries in SSA, spanning 1990 to 2017. The findings are as follows: (1) the analysis show that temperature has a positive and statistically significant effect on outmigration in agriculture-dependent nations. (2) the analysis shows that agricultural-value-added as a share in GDP has a negative and statistically significant effect on outmigration in agriculture-dependent nations. (3) the results also show that geographic location, and development level of a country, in addition to dependency on agriculture are key factors in the climate change–international migration nexus. Policy implications are discussed.
Keywords: F22; J61; Q50; Q54; 330; International migration; Sub-Saharan Africa; South Africa; Climate change; Agriculture